2019
DOI: 10.1519/jsc.0000000000002114
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Physical Qualities for Speed and Change of Direction Ability in Elite Female Soccer Players

Abstract: The purpose of this study was to determine the importance of physical qualities for speed and change of direction (CoD) ability in female soccer players. Data were collected on 10 female soccer players who were part of a professional English Women's Super League team. Player assessments included anthropometric (stature and body mass), body composition (dual-energy X-ray absorptiometry), speed (10m, 30m sprint), CoD ability (505 agility), aerobic (Yo-Yo Intermittent Recovery Test), lower-body strength (bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 30 publications
(28 reference statements)
5
83
2
1
Order By: Relevance
“…The IMTP ABS had the strongest correlation with SMBT performance and explained the most variance, likely due to the same absolute load used for all participants (four kg medicine ball). Despite the relationship between maturity and absolute strength, previous studies indicate measures of relative strength do not improve with increasing chronological age groups in boys [20] or girls [17], or maturity status of girls [45]. Therefore, our findings suggest that developing strength relative to body mass should be a primary goal of long-term athletic development programs, as supported by previous reviews [2,3] and position statements [46].…”
Section: Discussionsupporting
confidence: 78%
“…The IMTP ABS had the strongest correlation with SMBT performance and explained the most variance, likely due to the same absolute load used for all participants (four kg medicine ball). Despite the relationship between maturity and absolute strength, previous studies indicate measures of relative strength do not improve with increasing chronological age groups in boys [20] or girls [17], or maturity status of girls [45]. Therefore, our findings suggest that developing strength relative to body mass should be a primary goal of long-term athletic development programs, as supported by previous reviews [2,3] and position statements [46].…”
Section: Discussionsupporting
confidence: 78%
“…Age, body mass, height, fat mass and BMI of the players in this study were within the range previously reported in the literature for male elite soccer players (age: 22.1-28.1 years, body mass: 69.4-83.4 kg, height: 1.71-1.83, fat mass: 8.0-13.2, BMI: 20.8-22.9) [41]. Although previous studies showed the importance of anthropometric characteristics as an attribute for soccer performance in women elite players [42] and youth male players [43], few studies were found with the association between anthropometric characteristics and variables of soccer performance or players workload index in male elite players.…”
Section: Body Compositionmentioning
confidence: 61%
“…Regarding physical performance indicators, centripetal force and changes of direction are two essential components in team sports, allowing for the players to get ahead in the duel over the ball and create or block clear opportunities to get a goal [3,4]. For this reason, different research has investigated to what extent the training of different variables influences the performance of changes of direction, such as strength training of the lower limbs [51], trunk stability [52], or gait biomechanics [12][13][14]. However, the question is whether it is worth improving performance in changes of direction and centripetal force, and if they have an effect on performance during the competition.…”
Section: Discussionmentioning
confidence: 99%